Mecanismos de toxicidade dos metabólitos do fipronil, dessulfinil e sulfona, em mitocôndrias isoladas de fígado de rato - Tavares, Marco Aurélio [UNESP] (2015)
Fipronil is an insecticide extensively used to control pests in crops and animals. There are relates of poisoning due to exposure of fipronil in mammals and the liver is a potential target. In this study, we evaluated the effects of metabolites of fipronil, fipronildesulfinyl and fipronilsulfone on the bioenergetics, reactive oxygen species production and calcium efflux from mitochondria isolated from rat liver. Desulfinyl (5 to 25 μM) inhibited state-3 respiration in mitochondria energized with glutamate plus malate, substrates of complex I of the respiratory chain, and decreased the mitochondrial membrane potential resulting in inhibition of. Synthesis. Desulfinyl also caused uncoupling in succinate-energized mitochondria and calcium efflux. The metabolitesulfone also acted as mitochondrial inhibitors and uncouplers and caused calcium efflux, but inlower concentrations (0.5 to 5 μM). These effects of metabolites of fipronil on mitochondrial bioenergetics and calcium homeostasis may be related to toxic effects of the insecticide in the liver